Bibliometric Analysis of Anxiety and Physical Education in Web of Science—A Performance and Co-Word Study - Josué González-Ruiz; Antonio Granero-Gallegos; José-Antonio Marín-Marín; Antonio José Moreno-Guerrero (Pediatric Reports)
This study conducts a comprehensive bibliometric analysis of the concepts ‘physical edu- cation’ and ‘anxiety’ (PHYEDU_ANX) in the Web of Science (WoS) database. Background/Objectives: No previous biblio- metric studies were found that addressed this intersection, so this research is a pioneering exploration of this knowledge gap. The aim of the study is to examine the presence of both concepts in the scientific literature, identifying their trends, approaches, and future prospects. Methods: For this purpose, the methodology of co-word analysis was used. Results: The results of the study show that research on PHYEDU and ANX has traditionally focused on three main areas: motivation, exercise, and depression. In this first period, the focus was on the problem (ANX, depression…), Conclusions: whereas nowadays, research focuses on the subjects who suffer from it, mainly adolescents and students. The study suggests that future research in this field will focus on the areas of satisfaction, intervention, and association. This research also answers questions relevant to the field, such as which institutions or countries are the most prolific publishers of PHYEDU_ANX, as well as the most cited authors in this area of study.